Fine-Bubble–Slug-Flow Hydrogenation of Multiple Bonds and Phenols - Iio, Takuya; Nagai, Kohei; Kozuka, Tomoki; Sammi, Akhtar Mst; Sato, Kohei; Narumi, Tetsuo; Mase, Nobuyuki (Synlett, 2020)
We describe a promising method for the continuous hydrogenation of alkenes or alkynes by using a newly developed fine-bubble generator. The fine-bubble-containing slug-flow system was up to 1.4 times more efficient than a conventional slug-flow method. When applied in the hydrogenation of phenols to the corresponding cyclohexanones, the fine bubble–slug-flow method suppressed over-reduction. As this method does not require the use of excess gas, it is expected to be widely applicable in improving the efficiency of gas-mediated flow reactions.
Keywords: flow reaction; gas–liquid reaction; hydrogenation; alkynes; alkenes; phenols